2016
DOI: 10.1016/j.bbi.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of stress on microglial cell activation in male and female medial prefrontal cortex

Abstract: Susceptibility to stress-linked psychological disorders, including post-traumatic stress disorder and depression, differs between men and women. Dysfunction of medial prefrontal cortex (mPFC) has been implicated in many of these disorders. Chronic stress affects mPFC in a sex-dependent manner, differentially remodeling dendritic morphology and disrupting prefrontally mediated behaviors in males and females. Chronic restraint stress induces microglial activation, reflected in altered microglial morphology and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
122
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(131 citation statements)
references
References 57 publications
8
122
0
Order By: Relevance
“…Finally, it has to be considered that discrepancies in the literature could also arise from the age, sex or environmental conditions, including health/housing status of the animals used. Microglia react to stress stimuli (Bollinger, Bergeon Burns, & Wellman, ; Tian et al, ) and may undergo genotype‐specific changes following different types of environmental challenges (Hellwig et al, ; Maggi et al, ; Milior et al, ; Reshef et al, ; Winkler et al, ). Collectively, the described heterogeneities could explain some area‐ and context‐dependent microglia properties.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has to be considered that discrepancies in the literature could also arise from the age, sex or environmental conditions, including health/housing status of the animals used. Microglia react to stress stimuli (Bollinger, Bergeon Burns, & Wellman, ; Tian et al, ) and may undergo genotype‐specific changes following different types of environmental challenges (Hellwig et al, ; Maggi et al, ; Milior et al, ; Reshef et al, ; Winkler et al, ). Collectively, the described heterogeneities could explain some area‐ and context‐dependent microglia properties.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence in the literature that supports inflammatory mediators and immune cells as principle regulators of brain sexual differentiation, other than just neurotransmitters and sex hormones 26 . Acute and chronic stress can induce microglial cell mediated immune activation and inflammation in the brain, and recent studies have demonstrated sex differences in microglial density, function, and morphology in several brain regions 27 . Sex-specific association of oxidative stress and inflammation is also observed in other vascular-related diseases 10 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, stress has been reported to both de-ramify and hyper-ramify microglia, to increase and decrease cell size, and to increase and decrease Iba1 levels [33, 45, 50, 73, 74]. Differences may be due to the method used to detect microglia morphology.…”
Section: Discussionmentioning
confidence: 99%